The uses and gratifications of beef cattle breed association magazines for United States beef cattle producers - Underwood, Megan Renee (Kansas State University, 2022)
The United States beef industry is a major stakeholder in the current status and future of national and international agriculture. The beef industry is driven by technological innovations and beef producers in all 50 states. Beef cattle breed associations are essential to the success of the industry as they not only maintain breed pedigrees, but also serve as a vital source for information dissemination to their members. The official magazines of beef cattle breed associations are a primary source of communication for United States beef producers. Many beef breed association communication departments are working to strategize the future of their magazines to meet producer demands while minimizing expenses for print production and dissemination. This study sought to determine what information beef producers use beef breed association magazines for; topics beef producers want included in the magazines; differences in the uses and gratifications between junior and adult beef breed association members; differences based on operation characteristics; and producer perceptions of the magazines in a print vs. digital format. The theoretical framework used to guide this study was the uses and gratifications theory, which focuses on the reason why individuals choose to use a specific communication medium, the effect the medium has on the individual, and the gratifications received through its use. This study, the researcher focused on how United States beef producers use their beef breed association magazines, what information types they want to see more of, and preferences for magazine formats. The study utilized a descriptive quantitative survey research design to disseminate a Qualtrics questionnaire instrument to members of six United States beef breed associations. Questions included association membership status and association magazines received, how producers use information from their magazines, what topics beef producers want included in their magazines, operation characteristics, individual participant characteristics, and questions regarding junior beef breed association involvement. Results of the study revealed the uses and gratifications of beef breed association magazines in survey participant responses. Most United States beef cattle producers prefer their beef breed association magazines in a print format more than a digital version. Differences for using beef breed association print magazines were statistically significant between registered-purebred and cow-calf producers with a maternal trait focus when compared to other herd types and operation characteristics. Additionally, results showed beef producers use beef breed association magazines for information regarding topics of beef improvement strategies and genetic selection. Analysis of topics beef producers want to see more of in beef breed association magazines revealed significance to the findings of this study. It is recommended beef cattle breed associations continue to produce their magazines in a print format and include editorial topics curated to the needs of the beef producers using their magazines. The results revealed statistically significant uses for the beef breed association magazines regarding topics related to breed associations and should be used to guide the editorial content of the magazines moving forward. Future researchers should perform a content analysis analyzing the editorial content of beef breed association magazines to determine alignment with the results from this study.
Keywords: Communication; Beef producers; Magazines; Uses and gratifications; Breed associations; Beef industry